A transactional perspective on the everyday use of technology by people with learning disabilities. Issue 2 (3rd April 2023) - Barlott, Tim; MacKenzie, Paige; Goullon, Damian Le; Campbell, Liam; Setchell, Jenny
ABSTRACT: Research points to the potential benefit of information and communication technologies (ICTs) for people with learning disabilities. However, there has been limited exploration of the interconnected nature of people and social context when considering how people with learning disabilities use ICTs. The result has been an overemphasis on (and assumptions of) the skill limitations and individual capacity of people with learning disabilities and their use of ICTs. Using a transactional perspective based on the work of John Dewey, this study aimed to explore the interrelationship of people with learning disabilities, ICTs, and the social world. Using a post-qualitative and theory-driven approach, we employed a transactional perspective (namely the interrelated concepts of embodiment, habit, and growth ) to analyse interview data from 10 adult participants with learning disabilities. Our analysis suggested that when people have access and opportunity to co-mingle with technology, the technology can become embodied (feel like a part of them). ICTs were found to become an extension of participants' bodies, enhancing their literacy, learning, and connection with others. Introducing the concept of conjoint action, we explored how human and nonhuman bodies are enmeshed in the formation of what we typically think of as human habits. Participants developed more-than-human habits of ICT use that they drew from to coordinate with their everyday life, navigating everyday challenges. Yet, in restrictive social contexts (or those influenced by underlying assumptions of the vulnerability of people with learning disabilities), participants were less likely to embody ICTs in the rhythms of everyday life and experience benefits of ICT use. Our findings shed light on the entangled, transactional relationship of people and the social world, and present occupation as the conjoint action of human and nonhuman bodies.